Observaciones de Charadriiformes en el sur de la provincia de Buenos Aires, Argentina - Delhey, Kaspar J. V.; Petracci, Pablo F.; Pérez, Cristian H. F. (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.